2003
DOI: 10.1002/app.12960
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of new polymers from heterocyclic compounds and reactive solvents of melamine

Abstract: Reactive solvents were obtained from reactions of acetone with formaldehyde. They were used for the dissolution of some heterocyclic compounds. When the dissolution of the obtained compounds was not possible, the structures of these compounds were modified to increase their solubility. The oligomers cured at 80 -120°C in the presence of an acidic catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…We found that the stronger the acidity of XAH was, the more facile was the release of the formaldehyde. 7 The presence of two labile formaldehyde molecules in HMBA suggested that the parent BA molecule (from which the HMBA was synthesized) had two clearly acidic protons. On the basis of the determination of formaldehyde, it was not possible to recognize which of the two groups, iNAH or iC 5 AH, were responsible for the formaldehyde release.…”
Section: Formaldehyde Determinationmentioning
confidence: 99%
“…We found that the stronger the acidity of XAH was, the more facile was the release of the formaldehyde. 7 The presence of two labile formaldehyde molecules in HMBA suggested that the parent BA molecule (from which the HMBA was synthesized) had two clearly acidic protons. On the basis of the determination of formaldehyde, it was not possible to recognize which of the two groups, iNAH or iC 5 AH, were responsible for the formaldehyde release.…”
Section: Formaldehyde Determinationmentioning
confidence: 99%
“…Mechanistic studies revealed that melamine dissolved in this solvent by reacting with it and forming a resin-like solution. 2,3 The resulting solutions could be cured with acidic catalysts to yield new melamine-formaldehyde-ketone polymers suitable for preparation of expanded materials 7 or coatings 8,9 of high water resistance. 10 In this report, we concentrate on the possibility of applying melamine-formaldehyde-butanone (Mel-F-MEK) resins, i.e., the resins prepared by dissolving melamine in formaldehyde-MEK RSs 6 as materials for coatings of high hot water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxymethyl derivatives of ketones were used to dissolve and derivatize phenol and carbazole . Particularly, acetone was used because our preliminary attempts evidenced that, already at 40 °C, acetone reacted with formaldehyde to give product HMA ( I ) with subsequent release of formaldehyde on heating at ca 90–100 °C (Scheme ) . The released formaldehyde reacts with carbazole to give HMC (Scheme ).…”
Section: Introductionmentioning
confidence: 99%